2018
DOI: 10.1002/ajmg.a.40642
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on sleep‐disordered breathing in Morquio‐A syndrome

Abstract: Respiratory problems are common in Morquio-A syndrome (MPS IVA) but objective data on sleep-disordered breathing are scarce. The aim of our study was to review polygraphic (PG) findings and the need for noninvasive continuous positive airway pressure (CPAP) or noninvasive ventilation (NIV) in children with MPS IVA. A retrospective review of the clinical charts and PG of 16 consecutive children (7 boys, mean age 10.5 AE 4.2 years) with MPS IVA seen over a period of 3 years was performed. The prevalence of obstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In the present study, CSA was observed in only two patients (MPS IVA/MPS VI: 1/1) who had no history of neurologic deficit or cervico‐occipital surgery and the cause of the CSA was unknown. Facchina et al (2018) defined CSA in a patient with MPS IVA who had cervico‐occipital decompression, Nashed et al (2009) presented a patient with MPS I with both OSA and CSA in their study, and Kurihara et al (1992) showed CSA in a patient with MPS II whose brain biopsy revealed dilated lateral ventricles and diffuse atrophy with massive accumulation of gangliosides in the neurons. Central sleep apnea may be due to cervico‐occipital decompression and respiratory center dysfunction caused by glycosaminoglycan deposition in patients with MPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, CSA was observed in only two patients (MPS IVA/MPS VI: 1/1) who had no history of neurologic deficit or cervico‐occipital surgery and the cause of the CSA was unknown. Facchina et al (2018) defined CSA in a patient with MPS IVA who had cervico‐occipital decompression, Nashed et al (2009) presented a patient with MPS I with both OSA and CSA in their study, and Kurihara et al (1992) showed CSA in a patient with MPS II whose brain biopsy revealed dilated lateral ventricles and diffuse atrophy with massive accumulation of gangliosides in the neurons. Central sleep apnea may be due to cervico‐occipital decompression and respiratory center dysfunction caused by glycosaminoglycan deposition in patients with MPS.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme replacement therapy is recommended as the standard therapy for MPS I, II, VIA, and VI (Harmatz et al, 2004; Lin, Chen, Chuang, et al, 2010b; Lin, Chen, Lin, et al, 2010a; Ohashi, 2012; Rapoport & Mitchell, 2017). ERT has been shown to improve sleep apnea (Facchina et al, 2018; Lin, Chen, Chuang, et al, 2010b; Lin, Chen, Lin, et al, 2010a). We could not draw any firm conclusions about the efficacy of ERT in reducing the severity or preventing OSA in patients with MPS IVA and MPS VI because our cohort consisted of patients who were under ERT.…”
Section: Discussionmentioning
confidence: 99%